2014
DOI: 10.1111/eci.12368
|View full text |Cite
|
Sign up to set email alerts
|

DPPIV (CD26) as a novel stem cell marker in Ph+ chronic myeloid leukaemia

Abstract: The concept of leukaemic stem cells (LSCs) has been developed to explain the complex cellular hierarchy and biology of leukaemias and to screen for pivotal targets that can be employed to improve drug therapies through LSC eradication in these patients. Some of the newly discovered LSC markers seem to be expressed in a disease-specific manner and may thus serve as major research tools and diagnostic parameters. A useful LSC marker in chronic myeloid leukaemia (CML) appears to be CD26, also known as dipeptidylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 57 publications
2
77
1
1
Order By: Relevance
“…In regard to prognostic scores, Janssen et al found that patients with residual HSCs showed significantly better EUTOS and EURO-scores [15]. In contrast, we found no such relationship for our 3 groups, and similarly no correlation was previously found when considering only the percentage of CD26 + SCs [17]. …”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…In regard to prognostic scores, Janssen et al found that patients with residual HSCs showed significantly better EUTOS and EURO-scores [15]. In contrast, we found no such relationship for our 3 groups, and similarly no correlation was previously found when considering only the percentage of CD26 + SCs [17]. …”
Section: Discussioncontrasting
confidence: 70%
“…Recently, Herrmann et al analyzed various surface antigens that were formerly hypothesized to define CML LSCs [17]. CD26 was reported to provide the highest specificity, which was confirmed by a series of thorough experiments including long-term culture-initiating cell (LTC-IC) and xenotransplantation assays.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, an increase in CD26 expression was also observed, which was confirmed by the qPCR technique [25]. This result was also confirmed in another study with LSC, where CD26 showed high expression together with BCR/ABL1, an oncoprotein considered essential for CML manifestation [20,33].…”
Section: Resultssupporting
confidence: 63%